DEVELOPING POCKET E-BOOK TO IMPROVE RETELLING SKILLS OF FOLKLORES FOR HIGH SCHOOL STUDENTS - Silvia Yulianti; Ahmad Fadly (SEAQIL Journal of Language Education, 2023)
The primary issue addressed in this research revolves around the absence of folklore books suitable for educational purposes in high schools. Consequently, the research objective focuses on developing an e-book designed to enhance high school students' proficiency in retelling folklore narratives. Employing a Research and Development (R&D) approach, the researchers engaged in data collection and analysis, product design, validation, revisions, testing, and the eventual production of the e-book. The data for this research includes various folklore sources, namely, "Telaga Warna," "Karang Nini," "Bale Kambang," and "Situ Bagendit." These sources were collected through observational techniques, interviews, questionnaire distributions, and validation tests in developing the product. The outcomes of this developmental research attained a 'very feasible' categorization, evident in the material feasibility assessment achieving 80% and the endorsement from media experts reaching 98%. Moreover, the evaluation conducted by Indonesian language teachers yielded an 88% score, while student respondents' assessment of the media resulted in an 86% score. Based on these assessment outcomes, it can be concluded that this e-book media is well-suited for educational use within school.